Ageing and inflammation in patients with HIV infection. (9th August 2016) - Nasi, M.; De Biasi, S.; Gibellini, L.; Bianchini, E.; Pecorini, S.; Bacca, V.; Guaraldi, G.; Mussini, C.; Pinti, M.; Cossarizza, A.
Summary: Nowadays, HIV + patients have an expected lifespan that is only slightly shorter than healthy individuals. For this reason, along with the fact that infection can be acquired at a relatively advanced age, the effects of ageing on HIV + people have begun to be evident. Successful anti‐viral treatment is, on one hand, responsible for the development of side effects related to drug toxicity; on the other hand, it is not able to inhibit the onset of several complications caused by persistent immune activation and chronic inflammation. Therefore, patients with a relatively advanced age, i.e. aged more than 50 years, can experience pathologies that affect much older citizens. HIV + individuals with non‐AIDS‐related complications can thus come to the attention of clinicians because of the presence of neurocognitive disorders, cardiovascular diseases, metabolic syndrome, bone abnormalities and non‐HIV‐associated cancers. Chronic inflammation and immune activation, observed typically in elderly people and defined as 'inflammaging', can be present in HIV + patients who experience a type of premature ageing, which affects the quality of life significantly. This relatively new condition is extremely complex, and important factors have been identified as well as the traditional behavioural risk factors, e.g. the toxicity of anti‐retroviral treatments and the above‐mentioned chronic inflammation leading to a functional decline and a vulnerability to injury or pathologies. Here, we discuss the role of inflammation and immune activation on the most important non‐AIDS‐related complications of chronic HIV infection, and the contribution of aging per se to this scenario. Abstract : HIV + patients can present neurocognitive disorders, cardiovascular diseases, metabolic syndrome, bone abnormalities, and non‐HIV associated cancers. Chronic inflammation and immune activation that are typically observed in elderly people and were defined "inflammaging" can be present in HIV + patients, who experience a sort of premature aging, which affects heavily the quality of life. Main factors have been identified beside the traditional behavioral risk factors, that are the toxicity of antiretroviral treatments and chronic inflammation, leading to a functional decline and a vulnerability to injury or pathologies.